Az autofikció elevensége: (Bartók Imre: Jerikó épül) - Balajthy, Ágnes (Studia Litteraria, 2022)
This article analyses Imre Bartók’ Jerikó épül (“Jericho is being built”, 2018) in the context of contemporary Hungarian and international autofiction. Using the distinction established by Hannah Arendt and Giorgio Agamben between the notions of “bios” and “zoe” as a starting point, I argue that the novel deconstructs the logic of autobiographic narration via its expansion of the semantics of the term “life”, playing upon its evolutionary, biological and material connotations. Furthermore, identifying “the” as one of the book’s central, self-reflexive motifs, I explore its links to the most significant autobiographic tradition of European literature (hallmarked by the names of St. Augustine and Rousseau) and interpret it in the light of the text’s affective and performative functioning.